(untitled) (LEARNing Landscapes, 2017)
This article affirms the essential role of play for the well-being of children within the school context. The article explores the definition of play, why play is so important, gives examples of play in schools, and advocates for a child-centered approach to learning. The downside of a curriculum-centered approach is explored as an agent of anti-well-being for children. Standards and standardized tests are toxic to children’s healthy growth and development, crowding out or eliminating play from schools. The article advocates for a place for play in schools in order to promote the well-being of every child.